2007
DOI: 10.1104/pp.106.092205
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Screening of Arabidopsis Mutants Suggests the Lysine Histidine Transporter 1 to Be Involved in Plant Uptake of Amino Acids

Abstract: Plant nitrogen (N) uptake is a key process in the global N cycle and is usually considered a “bottleneck” for biomass production in land ecosystems. Earlier, mineral N was considered the only form available to plants. Recent studies have questioned this dogma and shown that plants may access organic N sources such as amino acids. The actual mechanism enabling plants to access amino acid N is still unknown. However, a recent study suggested the Lysine Histidine Transporter 1 (LHT1) to be involved in root amino … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
154
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 151 publications
(165 citation statements)
references
References 31 publications
10
154
1
Order By: Relevance
“…utes to the root import of several amino acids (19,20), might also be involved in m-tyrosine uptake from the medium. Inhibition of the shikimate pathway enzyme 3-deoxy-Darabino-heptulosonic acid 7-phosphate synthase by m-tyrosine in E. coli (21) suggested that similar effects could produce toxicity in plants.…”
Section: Resultsmentioning
confidence: 99%
“…utes to the root import of several amino acids (19,20), might also be involved in m-tyrosine uptake from the medium. Inhibition of the shikimate pathway enzyme 3-deoxy-Darabino-heptulosonic acid 7-phosphate synthase by m-tyrosine in E. coli (21) suggested that similar effects could produce toxicity in plants.…”
Section: Resultsmentioning
confidence: 99%
“…The lht1 mutant displayed accelerated leaf senescence (Svennerstam et al, 2007). Particularly when grown under a long photoperiod (16 h), early senescence was exclusively associated with old leaves, and the senescing leaves showed an enhanced oxidative burst, as detected by 3,3-diaminobenzidine (DAB) staining (see Supplemental Figures 6A to 6D online).…”
Section: The Lht1 Phenotypes Are Associated With Altered Redox Statusmentioning
confidence: 99%
“…Plant roots can take up amino acids (Wright, 1962) and the ecological significance of this ability has been recognized (Chapin et al, 1993;Näsholm et al, 1998;Schmidt and Stewart, 1999). Studies with Arabidopsis (Arabidopsis thaliana) mutants atlht1 and ataap1 provided molecular evidence that amino acid transporters facilitate uptake of amino acids into roots (Hirner et al, 2006;Lee et al, 2007;Svennerstam et al, 2007). In addition to amino acids, more complex organic N sources may also be important.…”
mentioning
confidence: 99%